Explaining state constitutional changes - Tarr, G. Alan (Revista de Investigações Constitucionais, 2016)
The article aims to analyze the fundamentals and the methods of state constitutional changes in the United States. It recognizes a certain pattern in the political processes of state constitutional changes, but it also points out that, in each case, some specific social groups act more intensely. Furthermore, it analyzes how external political forces can influence changes in state Constitutions. Finally, it concludes that, as a rule, the United States is currently undergoing a period in which there is a certain resistance to the creation of new state Constitutions, with greater popular preference for specific changes in the existing Constitutions.